2007
DOI: 10.1021/cm0715390
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of LiCoO2 with and without “AlPO4” Nanoparticle Coating:  Combined STEM and XPS Studies

Abstract: AlPO 4 "-coated LiCoO 2 was shown to exhibit markedly improved capacity retention relative to bare LiCoO 2 upon cycling to 4.7 V. Scanning and transmission electron microscopy imaging showed that the coating thickness of "AlPO 4 "-coated LiCoO 2 varied from ∼10 to ∼100 nm. Energy-dispersive X-ray mapping revealed that the coating was not single-phase "AlPO 4 ", rather consisting of P-rich thick regions (∼100 nm) and Al-rich thin regions (∼10 nm). Detailed X-ray photoelectron spectroscopy (XPS) studies of the "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

36
232
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(276 citation statements)
references
References 54 publications
36
232
2
Order By: Relevance
“…27,28 The lattice oxygen at ≈529.5 eV, the surface oxygen species O-C = O * and Li 2 CO 3 collectively at ≈532.1 eV, the O * P(OR) 3 and O * -C = O species at ≈533.5 eV and Li x PF y O z at ≈534.6 eV are identified by the dashed lines (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…27,28 The lattice oxygen at ≈529.5 eV, the surface oxygen species O-C = O * and Li 2 CO 3 collectively at ≈532.1 eV, the O * P(OR) 3 and O * -C = O species at ≈533.5 eV and Li x PF y O z at ≈534.6 eV are identified by the dashed lines (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…However, this benefit can be temporary as recent work indicates that the Li-Al-Co-O surface region is consumed during cycling. 27 The "AlPO 4 "-coating on LiCoO 2 can induce the formation of Al-rich regions (LiAl y Co 1-y O 2 ) and P-rich regions (Li + conducting Li 3 PO 4 ), 28 and that Co-and Alcontaining oxyfluoride species and species like PF x (OH) y developed on the surface during cycling can lower the rate of Co dissolution and deposition of Co-containing species on the negative electrode and further degradation of LiPF 6 . 27 For a more detailed discussion of the * Electrochemical Society Active Member.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cho et al [86][87][88][89] pointed out that the cycling and thermal stability of cathode materials can be enhanced by surface modification with AlPO4· (PO4) 3− polyanions and Al 3+ with high electronegativity, which resist the side reaction with the electrolyte, and oxides with (PO4) 3− bonding are thermally stable, improving the cycling performance [88,90]. Besides, AlPO4 coating acts as a protective layer, reducing the surface exposure of cathode in the electrolyte, thus remitting metal dissolution and reducing oxygen generation [87,89,[91][92][93]. The application of AlPO4 coating involves various kinds of cathode materials, including LiCoO2, LiNi0.8Co0.1Mn0.1O2, LiMn1.5Ni0.5O4 (Fig.…”
Section: Alpo4mentioning
confidence: 99%
“…[21][22][23][24][25] In particular several studies have shown that AlPO 4 coatings of LiCoO 2 particles stabilizes the LiCoO 2 against charge to high potentials >4.2 V vs. Li/Li + . [26][27][28][29][30][31][32][33][34] Such stabilizing effects may extend to over-insertion of lithium into the cathode and thus an AlPO 4 coating on the surface of LiCoO 2 could have a dual utility of enhancing z E-mail: brian.landi@rit.edu overdischarge and overcharge tolerance of advanced lithium ion cells with added reversible lithium.In the present work, a solution deposited coating of AlPO 4 onto LiCoO 2 particles is tested for its utility in improving the tolerance of LiCoO 2 to over-insertion of lithium at potentials <3.0 V vs. Li/Li + . Half-cell testing in coin cells is used to study the effect of an AlPO 4 coating to stabilize a LiCoO 2 cathode discharge performance against a 5% (of the 140 mAh/g nominal capacity of LiCoO 2 ) over-insertion of lithium by fixed resistive load.…”
mentioning
confidence: 99%